Respuesta :
Answer: d.h=−4
PLZ MARK BRAINLIEST!
Step-by-step explanation:
Let's solve your equation step-by-step.
−3(h+5)+2=4(h+6)−9
Step 1: Simplify both sides of the equation.
−3(h+5)+2=4(h+6)−9
(−3)(h)+(−3)(5)+2=(4)(h)+(4)(6)+−9(Distribute)
−3h+−15+2=4h+24+−9
(−3h)+(−15+2)=(4h)+(24+−9)(Combine Like Terms)
−3h+−13=4h+15
−3h−13=4h+15
Step 2: Subtract 4h from both sides.
−3h−13−4h=4h+15−4h
−7h−13=15
Step 3: Add 13 to both sides.
−7h−13+13=15+13
−7h=28
Step 4: Divide both sides by -7.
−7h
−7
=
28
−7
h=−4
The solution to the equation -3(h + 5) + 2 = 4(h + 6) - 9 is Option(d) -4 .
How to find the solution of the given equation ?
Given equation is -3(h + 5) + 2 = 4(h + 6) - 9
Expanding the given expression and then solving for h ,
⇒ -3h - 15 + 2 = 4h + 24 - 9
⇒ -3h - 13 = 4h + 15
⇒ -7h = 28
∴ h = -4 .
Thus the solution to the equation -3(h + 5) + 2 = 4(h + 6) - 9 is Option(d) -4 .
To learn more about solution to an equation, refer -
https://brainly.com/question/9151865
#SPJ2